ANALYSIS OF THE ESSENCE AND VECTORAL APPLICATION OF THE CONTEXT APPROACH TO TEACHING OF THE COURSE «UKRAINIAN LANGUAGE FOR PROFESSIONAL PURPOSES» - Humeniuk, Iryna (Mountain School of Ukrainian Carpaty, 2019)
The article is devoted to the consideration of the methodical potential of a contextual approach to teaching of Ukrainian language for professional purposes. The actuality of the raised problem is caused by the necessity of preparation of a mobile specialist who is able to self-educate during their life. The article explains the definitions of the concepts «contextual learning technology», the place of this technology in the methodological system of the course is determined. The intention of this publication is to show the methodical opportunities of vector application of contextual approach to teaching of the Ukrainian language for professional purposes, carrying out a structural and semantic analysis of the essence of the term “contextual learning technology». To solve the above problems, a set of methods has been used: scientific abstraction, analysis and systematization of literary sources to find out the level of solving of this problem in the modern scientific space, terminological analysis to show the conceptual apparatus of the research, the methods of visualization and generalization. The author emphasizes the universality and the educational mobility of the course «Ukrainian Language for Professional Purposes», shows the necessity of usage of the applying a contextual approach to teaching of this course in the context of the integration into the European educational space. The special attention has been paid to discovering of the interdependence between mastering the tasks of the practical part of the discipline «Ukrainian Language (for Professional Purposes)», students’ independent work and productiveness of their acquiring of the communicative experience.